Optimization of CHB-STATCOM Power Ramp Given Response Time with Capacitance Reduction - Zhang, Huaen (International Journal of Mechanical and Electrical Engineering, 2025)
The capacitance-reduced H-bridge cascaded static synchronous compensator (CHB-STATCOM) uses ramp feedforward to suppress the phase-to-phase voltage unbalance of the dc-side voltage when the compensated power jumps, and its minimum transition time T is 10ms, which fails to satisfy the shortest transition time T is 10ms, which cannot meet the demand of fast response of the device. To address this problem, this paper gives the relationship between the commanded power tapering time T less than 10ms and the inter-phase DC voltage based on the CHB-STATCOM control principle of capacitance reduction. The equations on increasing the DC component under the constraints of the upper and lower boundary constraints are developed and the upper and lower boundary constraints are taken into account under the constraints of the CHB-STATCOM operating principle of decreasing capacitance value .According to the characteristics of the constraint equations, a method for solving the constraint equations is proposed, and the solution results are analyzed by specific examples. The effectiveness of the method in improving the response time is verified by simulation with MATLAB software. The conclusions of the study can also provide a reference for the device to select the power jump time.